Factors affecting Continued Participation in Tuberculosis Contact Investigation in a Low-Income,High-Burden Setting - Michelle May D. Goroh; Christel H.A. van den Boogaard; Mohd Yusof Ibrahim; Naing Oo Tha; Swe; Fredie Robinson; Khamisah Awang Lukman; Mohammad Saffree Jeffree; Timothy William; Anna P. Ralph (2020)
Setting: Outpatient clinics, Kota Kinabalu, Malaysia; January–April 2018. Objectives: To identify barriers to full participation in tuberculosis (TB) contact investigation. Methods: Cross-sectional study of knowledge, perceptions, and behaviours among TB contacts. This study was conducted among contacts who attended an initial clinic visit to explore retention in care. During this first visit, contacts were approached for participation in a questionnaire at a follow-up visit. Contacts who consented but did not subsequently attend were interviewed at home. Associations between questionnaire findings and attendance were tested using logistic regression. Results: Of the total 1436 identified contacts, 800 (56%) attended an initial clinic visit. Of 237 consenting TB contacts, 207 (87%) attended their follow-up appointment. In univariable analyses, the odds of attendance were highest for people notified to attend the TB clinic directly by a health inspector; close relatives of TB patients; non-students; people with higher incomes and smaller households; older individuals; males; and people not perceiving TB as stigmatising. In multivariable analysis, mode of notification to attend and having a close relative with TB remained significant. Conclusions: Health inspectors provide an effective role in TB contact investigation through direct personal communication to encourage the completion of the TB screening process, but this requires further integration with clinical processes, and with workplace and school-based investigations.